A Neglected Congenital Rubella Syndrome in 10-Year-Old Boy - Kafin Rifqi; Dicky Hermawan (Vision Science and Eye Health Journal, 2022)
Introduction: Cataract, congenital heart defect, and hearing impairment are the three most common manifestations of congenital rubella syndrome (CRS) that lead to developmental delay in the children. CRS usually present during the infant period of three months old as the median age number. Ironically, we found a 10-year-old boy who was diagnosed with CRS and there was no significant plan to improve his condition anymore because of his neglected by family. The purpose of this case report is to alert primary health workers and also ophthalmologists to do our best to prevent blindness due to cataracts in Indonesia with early detection. Case presentation: A 10-year-old boy was brought to the outpatient clinic with a chief complaint of difficulties in focusing the target in the classroom. The grandmother said that her grandson has already had a white plaque in his both eyes since he was born. The boy has also suffered from deaf-mutism. His visual acuity was hand movement and there was lens opacity in his both eyes. He also had posterior uveitis in both eyes followed by the presence of nystagmus. There was retinal detachment in ultrasonography (USG) examination. The patient has no cardiac abnormalities. Rubella infection was confirmed by the high number of IgG rubella serology. His grandmother had just brought the boy to the outpatient clinic because she never thought that the eyes needed therapy until the boy could not do his daily activities as the cataract worsen. Conclusions: The parent’s role is highly crucial for the visual outcome of patient with congenital ophthalmologic problems. Primary health worker also play a significant role in early detection that may prevent such incident. Delayed detection and management of congenital cataracts may cause permanent visual impairment and lead to patient’s poor quality of life.